Disruptions in preventive care: Mammograms during the COVID‐19 pandemic. (4th November 2020) - Song, Hummy; Bergman, Alon; Chen, Angela T.; Ellis, Dan; David, Guy; Friedman, Ari B.; Bond, Amelia M.; Bailey, Julie M.; Brooks, Ronald; Smith‐McLallen, Aaron
Abstract: Objective: To measure the extent to which the provision of mammograms was impacted by the COVID‐19 pandemic and surrounding guidelines. Data Sources: De‐identified summary data derived from medical claims and eligibility files were provided by Independence Blue Cross for women receiving mammograms. Study Design: We used a difference‐in‐differences approach to characterize the change in mammograms performed over time and a queueing formula to estimate the time to clear the queue of missed mammograms. Data Collection: We used data from the first 30 weeks of each year from 2018 to 2020. Principal Findings: Over the 20 weeks following March 11, 2020, the volume of screening mammograms and diagnostic mammograms fell by 58% and 38% of expected levels, on average. Lowest volumes were observed in week 15 (April 8 to 14), when screening and diagnostic mammograms fell by 99% and 74%, respectively. Volumes began to rebound in week 19 (May), with diagnostic mammograms reaching levels to similar to previous years' and screening mammograms remaining 14% below expectations. We estimate it will take a minimum of 22 weeks to clear the queue of missed mammograms in our study sample. Conclusions: The provision of mammograms has been significantly disrupted due to the COVID‐19 pandemic.